2022
DOI: 10.1210/jendso/bvac088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of the Growth Hormone–Releasing Peptide-2 Test for Hypothalamic-Pituitary Disorder

Abstract: Purpose Growth hormone deficiency (GHD) develops early in patients with hypothalamic-pituitary disorder and is frequently accompanied by other anterior pituitary hormone deficiencies including secondary adrenal insufficiency (AI). A growth hormone-releasing peptide-2 (GHRP2), which is wildly used for the diagnosis of patients with GHD, has been considered to induce not only growth hormone (GH) release but also ACTH release. However, its clinical usefulness in hypothalamic-pituitary disorder i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Previous studies have assessed the GST in identifying GHD in adult patients with pituitary disorders and reported that GH cut-offs between 2.5 and 3 μg/L provided good sensitivity and specificity ( 54 , 55 , 56 ). There have also been other studies that suggest that using a GH cut-off of 3 μg/L overdiagnoses adult GHD in overweight/obese subjects ( 57 , 58 ).…”
Section: Growth Hormone Stimulation Testsmentioning
confidence: 99%
“…Previous studies have assessed the GST in identifying GHD in adult patients with pituitary disorders and reported that GH cut-offs between 2.5 and 3 μg/L provided good sensitivity and specificity ( 54 , 55 , 56 ). There have also been other studies that suggest that using a GH cut-off of 3 μg/L overdiagnoses adult GHD in overweight/obese subjects ( 57 , 58 ).…”
Section: Growth Hormone Stimulation Testsmentioning
confidence: 99%
“…The normal response of ACTH to the CRH test indicated hypothalamic-adrenal insufficiency. In addition, the low peak cortisol level with normal ACTH response after GHRP2 administration indicated hypothalamic-adrenal insufficiency [31]. This diagnosis was confirmed based on the absence of ACTH response and the peak cortisol level <18 μg/dL in the ITT.…”
Section: Discussionmentioning
confidence: 83%
“…A total of 20 cases applied either the GHRP-2 test or the GRF test or both. Three cases reported a maximum GH concentration of <16 ng/ml, which was lower than the diagnosis criteria in the GHRP-2 test ( 8 ). The time to peak values usually occurred at 15 to 60 min.…”
Section: Resultsmentioning
confidence: 93%
“…GHRP-2 is available in Japan and widely used by Japanese researchers. The results of the GHRP-2 test are classified as non-GHD (peak GH > 16 ng/ml), moderate GHD (9 ng/ml < peak GH ≤ 16 ng/ml), and severe GHD (peak GH ≤ 9ng/ml) ( 8 ). Since most of the provocative tests were performed in Japan, the above diagnostic criteria apply to these patients in our review.…”
Section: Discussionmentioning
confidence: 99%